Viability of fungal cultures maintained at -70 degrees C. - Pasarell, L (1992)
One thousand four hundred forty-seven clinical and environmental isolates of molds, yeasts, aerobic actinomycetes, and algae belonging to 164 genera (382 taxa) maintained on potato dextrose agar at -70 degrees C for periods ranging from 6 months to 13 years were subcultured and then incubated at 25 degrees C to determine their viabilities. Thirty-three isolates, Alternaria alternata (n = 1), Apophysomyces elegans (n = 1), Bipolaris spicifera (n = 1), Blastomyces dermatitidis (n = 4), Cokeromyces recurvatus (n = 1), Coremiella cubispora (n = 1), Cryptococcus ater (n = 1), Curvularia sp. (n = 1), Exserohilum monoceras (n = 1), Exserohilum pedicillatum (n = 1), Exserohilum rostratum (n = 1), Filobasidium floriforme (n = 1), Madurella mycetomatis (n = 1), Oedocephalum spp. (n = 2), Penicillium marneffei (n = 1), Pseudomicrodochium spp. (n = 4), Saksenaea vasiformis (n = 1), Sporothrix sp. (n = 1), and Mycelia Sterilia (n = 8), did not grow after repeated attempts at subculturing. Neither time in storage nor taxonomic classification was associated with a lack of viability. Storage at low temperature for either short or long periods of time is an excellent method for maintaining most medically important fungi.